SOSIALISASI INVESTASI PASAR MODAL PADA MUDA MUDI DESA BAKALAN KABUPATEN SUKOHARJO - Yuli Chomsatu Samrotun; Agni Astungkara; Tien Kartika Kumala Dewi Ramah Harnung Setiyawati, Silvia Dela Agusta (Jurnal Pengabdian Kepada Masyarakat "SIDOLUHUR", 2022)
Stock investment is an investment activity in the form of buying shares (securities) of a company. This service activity aims to add insight and provide education for youth youth in the village of Bakalan Polokarto Sukoharjo how to invest in the capital market through the Phitancro securities application. This is due to the lack of knowledge and understanding of youth organizations in the village. This service also provides a clear description of the importance of education and training on investment in the Indonesian capital market in Bakalan Polokarto village, Sukoharjo